Roots of resilience: my journey as a Conservation Agriculture champion - Kudzanai Chimhanda (International Maize and Wheat Improvement Center, 2024)
Conservation Agriculture promotes climate resilience, increased crop yields, and healthier plants, supporting livelihoods and food security across the region. Grace Malaicha tells her story.